Digital Learning Assessment: Investigating the Needs of Lecturers and Students in Teacher Professional Education Program - Supriyadi, Supriyadi; Dari, Tita Ratna Wulan; Sari, Armilia (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2023)
The advancement of technology demands that teachers use technological media and continuously explore their potential for making improvements in teaching. In line with this, the Teacher Professional Education Program (PPG) strives to bring about these improvements and is mandatory for prospective professional teachers to possess. Regrettably, the current PPG Program at FKIP Unsri lacks a digital assessment component. Hence, the significance of this research lies in identifying the needs of both students and lecturers for a digital assessment. The findings will contribute to the design of further developmental research, aiming to create a comprehensive set of assessment items tailored to the digital realm. The respondents were purposively taken based on one main criteria; they were active lecturers and students in the New Technologies for Teaching and Learning Course at PPG Unsri 2023. As the result, there were 2 lecturers and 46 students participating as research samples. A questionnaire was distributed to the respondents. It consisted of 16 questions divided into 5 aspects of data collection. The data obtained was then descriptively analyzed and interpreted. The result shows (1) students and lecturers require the development of interactive questions tools compared to those currently available in the LMS of PPG. (2) Students and lecturers agree that the developed product should be able to assess students’ understanding in the cognitive/knowledge domain at various levels of Bloom’s Taxonomy. Based on the assessment by lecturers, the development of questions will vary from level C3 to C6. However, it is not ruled out that there may be questions of LOTS level included. (3) Students and lecturers are familiar with the use of the LMS as a digital tool in assisting learning. Therefore, there should be a further research design in developing the digital learning assessment for the course.